KAJIAN KOMPARATIF PENERAPAN GREEN CAMPAIGN DI ASIA TENGGARA - Yohannes Cahyadi (Universitas Trunojoyo Madura, 2016)
Environmental condition in the world become worst dan under threat. The main cause of this damage is garbage problem. Therefore, This article is expected to help government to share the information about go green campaign and expected that people can understand the importance of preserving the environment. To solve that garbage problem, the world need a good anticipation, one of the ways is to apply green campaign concept. This green campaign can be does with many ways, consist of green marketing program, go green campaign, and many more. Firm regulation and the application of fines for noncompliance is the key to success to implementing green campaign in many countries.